Nanomedicine Strategies for Sustained, Controlled and Targeted Treatment of Alzheimer's Disease - Ma, Tian-Jun; Gao, Jie; Liu, Yan; Zhuang, Jian-Hua; Yin, Chuan; Li, Peng; Mao, Lei; Xu, Jin; Xu, Yi-Xin; Li, Yan-Peng; Zhao, Zhong-Xin; Yin, You (Mini Reviews in Medicinal Chemistry, 2018)
Background: Alzheimer's disease (AD) is one of the most devastating diseases worldwide. The current drugs for AD can only ameliorate the symptoms rather than reverse or prevent the progress of AD. On the other hand, blood-brain barrier (BBB), as a natural barrier, significantly impedes drug delivery from the blood circulation into the brain. Nanomedicine can be a safe, effective and promising approach to treat AD. Objective: This review summarizes the recent nanomedicine research in this area, including the use of liposomes and nanoparticles (NPs), to provide new approach for targeted treatment of AD. Method: Collecting and referring to the related literature in recent 10 years, via searching MeSH Terms “Alzheimer's disease; nanomedicine; nanoparticle; amyloid β peptide; tau protein; autophagy”. Results: Nanomedicines show superiority over conventional anti-AD drugs as a potential weapon against AD by the five proposed mechanisms: many unfavorable pharmaceutical properties of conventional anti-AD drugs maybe greatly overcome by nanomedicine; nanomedicines trigger efficient production of high-titer anti-Aβ antibodies following controlled release of antigens by them; some apolipoprotein- based nanomedicines could preferably bind to Aβ and increase the elimination of Aβ; nanomedicine-induced autophagy could be facilitated to increase the elimination of Aβ; nanomedicineinduced inhibition of tau aggregation. Conclusion: Therefore, nanomedicine-mediated drug therapy is promising in the treatment of AD.
Keywords: tau protein